Vitamin E inhibits inflammation and improves immune response of mud crabs (Scylla paramamosain) by activating an antioxidant enzyme system and apoptosis mechanism - Xiangkai Li; Shichao Xie; Yuhang Yang; Zheng Tang; Yinqiu Tian; Haiqing Cao; Tingting Zhu; Min Jin; Peng Sun; Qicun Zhou (Animal Nutrition)
An 8-week feeding trial was conducted to evaluate the effects of dietary vitamin E levels on growth, antioxidant status and immune response for mud crabs (Scylla paramamosain). A total of 180 mud crabs (initial weight: 24.16 ± 1.08 g) were fed six different dietary vitamin E levels, where the analyzed vitamin E were 9.65, 34.70, 58.50, 76.30, 102.00 and 199.00 mg/kg, respectively. The results showed that crabs fed with the 76.30 mg/kg vitamin E diet exhibited significantly higher final weight (P = 0.007), percent weight gain (PWG) (P = 0.008) and specific growth rate (P = 0.010) than those fed the diets with 9.65 and 34.70 mg/kg vitamin E. The highest activities of total antioxidant capacity in hemolymph (P = 0.006) and hepatopancreas (P = 0.017), and superoxide dismutase (SOD) (P = 0.037) in hemolymph were observed in crabs fed the 76.30 mg/kg vitamin E diet, and crabs fed the diet with 102.00 mg/kg vitamin E showed higher activities of peroxidase (POD) (P = 0.006) and α-tocopherol transfer protein (P = 0.024) in hemolymph than those fed the other diets. Dietary 76.30 mg/kg vitamin E significantly up-regulated the expression of cat, gpx, prx and CytMn-sod in hepatopancreas (P < 0.01). The expression levels of genes related to pro-inflammatory factor (il-16, litaf, rab6a and relish) in hepatopancreas were significantly down-regulated and the expression level of anti-inflammatory factor related gene (tgf) significantly up-regulated in crabs fed diet with 199.00 mg/kg vitamin E (P < 0.05). Crabs fed the diet with 76.30 mg/kg vitamin E exhibited the highest percentage of survival cells in hemocytes (P = 0.026). The mRNA expression level of genes related to pro-apoptotic cytokines (bax and bok) significantly down-regulated, and the mRNA expression level of anti-apoptotic cytokines related genes (pi3k, akt and bcl-2) significantly up-regulated with dietary vitamin E levels increasing from 9.65 to 76.30 mg/kg (P < 0.05). In conclusion, the quadratic regression model based on PWG indicated that the optimal requirement of vitamin E was 99.13 mg/kg for the mud crab. Moreover, dietary 58.50 and 76.30 mg/kg vitamin E inhibited the inflammatory response and improved the immune response.